The Impact of System Quality and User Satisfaction: The Mediating Role of Ease of Use and Usefulness in E-Learning Systems - Fitria, Fitria; Yahya, Muhammad; Ali, M. Ichsan; Purnamawati, Purnamawati; Mappalotteng, Abdul Muis (International Journal of Environment, Engineering and Education, 2024)
The research aims to understand how the system's quality influences users' perceptions of its usability and ease of use, affecting their overall satisfaction with the e-learning system. This analysis provides insights into the factors contributing to a positive user experience and the sustainable use of e-learning platforms. The study employs a quantitative approach with a survey method. The sample comprises 470 students from five universities using e-learning information systems, selected through purposive sampling. Data was collected via a questionnaire survey distributed to respondents and analyzed using Structural Equation Modeling (SEM) with the IBM AMOS Program. The results indicate that System Quality (SYQ) significantly affects Perceived Ease of Use (PEOU) with a probability value of 0.019 (p < 0.05), System Quality (SYQ) significantly affects Perceived Usefulness (PU) with a probability value of 0.036 (p < 0.05), Perceived Usefulness (PU) significantly affects User Satisfaction (USA) with a probability value of 0.028 (p < 0.05), and Perceived Ease of Use (PEOU) significantly affects User Satisfaction (USA) with a probability value of 0.000 (p < 0.05). The study concludes that integrating TAM and ISSM provides a comprehensive framework for understanding the factors influencing the sustainable use of e-learning systems. The practical implications of this research underscore the importance of giving e-learning systems that are not only easy to use and useful but also possess high system, information, and service quality to enhance user satisfaction and sustain usage.